Multiplexed Metasurfaces: Wavevector and Frequency Multiplexing Performed by a Spin‐Decoupled Multichannel Metasurface (Adv. Mater. Technol. 1/2020). Issue 1 (13th January 2020) - Xu, He‐Xiu; Hu, Guangwei; Jiang, Menghua; Tang, Shiwei; Wang, Yanzhao; Wang, Chaohui; Huang, Yongjun; Ling, Xiaohui; Liu, Haiwen; Zhou, Jiafeng
Abstract : In article number 1900710, He‐Xiu Xu and co‐workers propose a strategy to realize spin‐decoupled high‐capacity multifunctional metasurface by multiplexing the frequency and wavevector degree of freedom. By integrating both geometric and dynamic phases in a split ring resonator and crossbars in achessboard super metaatoms, the inherent limitation of spin‐flipped Pancharatnam–Berry profiles can be completely decoupled between two spin states. Two proof‐of‐concept metadevices are experimentally demonstrated both with the four‐port wavefront manipulations.